PENGELOLAAN KESAN MASKULINITAS PADA LAKI-LAKI FEMININ DI KOTA PEKANBARU - Azura, Sayyida; Sari, Genny Gustina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
When a man meets some women in group, it may look normal. However, when the man shows an attitude and behavior that is not naturally done by men in general, such as making a soft, seductive voice or being "girlish" while laughing in a high and loud voice that is normally done by women, although if we see him from the appearance, the man looks neat and fashionable like how men in general, we might have a different opinion about that man again. This phenomenon makes the writer interested in researching about man who have feminine characteristics. Various opinions and judgments will appear from someone who has interacted with feminine men. As posted by an anonymously person on his personal blog about his opinion to his male friend who has different hobbies since his childhood, to a psychologist who provide an explanation of why the feminine traits appear in men and how to handle them. This research aims to find out the motives for management of masculinity impression of feminine men, knowing the front stage, and the back stage of a feminine man in Pekanbaru City.This study uses qualitative research methods. The selection of the subject with the technique of snowball and produce two informants: FZ and HD. Data collection through the stage of observation by following the daily activities of the man who was behaving feminine, perform in depth interviews to corroborate the results, and then the documentation.Research results show that men have feminine motifs as a reason to manage appearance, first ‘because motive’ is the reason feminine man to be masculine because feminine man experience case bullying, discrimination, and labeling. second, ‘in order to motive’ is divided into three, namely self-esteem motive for wanting to be appreciated, the motif of the evaluation where the feminine looking men to themselves in the past, and the motives of the paradigm that is the expectation of a feminine man who wants to change the view that men would not necessarily have the feminine sexual orientation that is distorted. Front stage is someone who wants to showing in accordance with the expectations and values of who wants to be seen by the public and the environment, in this case the feminine man will behave like masculine man in some places like in the general environment, in a workplace, even at home. Back Stage is where the feminine man show himself without the existence of attitudes in settings. In this study, the informants shows itself only when shared his closest friends and some family members.Keywords: Feminine Man, Masculine, Pekanbaru, Impression Management, Motive, Back Stage & Front Stage.